Tonsillar Microbiota: a Cross-Sectional Study of Patients with Chronic Tonsillitis or Tonsillar Hypertrophy - Shengru Wu (American Society for Microbiology, 2021)
ABSTRACT Chronic tonsillitis (CT) and tonsillar hypertrophy (TH) are common tonsillar diseases that are related to infection and inflammation. Little is known about tonsillar microbiota and its role in CT and TH. This study aims to identify palatine tonsillar microbiota both on the surface and in the core tissues of CT and TH patients. In total, 22 palatine tonsils were removed and collected from CT and TH patients who underwent surgery. The surface and core microbiota in the tonsils of CT and TH patients were compared using 16S rRNA gene sequencing of V3-V4 regions. Differential tonsillar microbiotas were found in the CT versus TH patients and surface versus core tissues. Further, a higher relative abundance of bacterial genera, including Haemophilus, Streptococcus, Neisseria, Capnocytophaga, Kingella, Moraxella, and Lachnospiraceae [G-2] in patients with TH and Dialister, Parvimonas, Bacteroidales [G-2], Aggregatibacter, and Atopobium in patients with CT, was observed. Of these, the differential genera of Dialister, Parvimonas, and Neisseria served as key factors in the tonsillar microbiota network. Notably, four representable tonsillar microbial types were identified, with one, consisting of a higher abundance of Haemophilus and Neisseria, exclusively detected in the TH patients. This study analyzed the different tonsillar microbiota from the surface and core tissues of CT and TH patients. Several bacteria and various microbial types related to CT and TH were identified, along with potential bacterial networks and related immune pathways. IMPORTANCE The human microbiota has been shown to be functionally connected to infectious and inflammation-related diseases. So far, only limited studies had been performed on tonsillar microbiota, although tonsils play an essential role in the human immune defense system and encountered numerous microorganisms. Our work presented different tonsillar microbiota from surface and core tissues of chronic tonsillitis (CT) and tonsillar hypertrophy (TH) patients. Notably, one tonsillar microbiota type, which contains a higher abundance of Haemophilus and Neisseria, was only detected in the TH patients. Furthermore, certain bacteria, such as Haemophilus, Neisseria, Dialister, and Parvimonas, may serve as microbial biomarkers to discriminate CT patients from TH patients. These data provide important microbiota data in the tonsillar research area and are highly useful for researchers both in the oral microbiome field and clinical field.